THERAPEUTIC ROLE OF BRYONIA ALBA AND RHUS TOXICODENDRON (30C) IN THE MANAGEMENT OF RHEUMATOID ARTHRITIS: A CASE SERIES - Dr. Santosh Reddy; Dr. Munjal Thakar; Dr. Poorav Desai; Dr.Ankur Desai (The Bioscan, 2025)
Background: Rheumatoid arthritis (RA) is a chronic, systemic autoimmune disorder characterized by symmetrical polyarthritis, leading to pain, swelling, stiffness, and progressive disability. Despite the availability of conventional therapies, limitations remain due to side effects and incomplete remission. Homoeopathy offers individualized remedies such as Bryonia- alba and Rhus- toxicodendron, frequently prescribed based on characteristic modalities. Objective: To evaluate the therapeutic role of Bryonia -alba and Rhus- toxicodendron (30C) in patients with RA through a case series approach. Methods: This case series includes patients diagnosed with RA based on American College of Rheumatology/European League against Rheumatism (ACR/EULAR) criteria. Patients were prescribed Bryonia-alba or Rhus -toxicodendron (30C) according to individualized symptom similarity. Each case was followed for six months, and disease activity was assessed using the Disease Activity Score-28 (DAS28). Results: Clinical improvement was observed in joint pain, swelling, and stiffness, with a reduction in DAS28 scores across cases. Patients treated with Bryonia- alba reported relief in symptoms aggravated by motion and relieved by rest, while those treated with Rhus- toxicodendron demonstrated improvement in symptoms aggravated by rest and ameliorated by movement. Conclusion: The case series highlights the potential role of Bryonia- alba and Rhus- toxicodendron (30C) in the management of RA, suggesting a beneficial effect in reducing pain and disease activity. Larger controlled studies are warranted to validate these findings.